2013
DOI: 10.1016/j.nucmedbio.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body pharmacokinetics of HDAC inhibitor drugs, butyric acid, valproic acid and 4-phenylbutyric acid measured with carbon-11 labeled analogs by PET

Abstract: The fatty acids, n-butyric acid (BA), 4-phenylbutyric acid (PBA) and valproic acid (VPA, 2-propylpentanoic acid) have been used for many years in the treatment of a variety of CNS and peripheral organ diseases including cancer. New information that these drugs alter epigenetic processes through their inhibition of histone deacetylases (HDACs) has renewed interest in their biodistribution and pharmacokinetics and the relationship of these properties to their therapeutic and side effect profile. In order to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 44 publications
1
71
0
Order By: Relevance
“…In addition, VPA was used as the total HDACs inhibitor to detect the cardioprotection in the OVE26 type 1 diabetes mice too. Although butyrate was used in the previous studies as total HDAC inhibitor (15), pharmacokinetic studies have confirmed its lower cardiac distribution, compared to VPA (41, 42). In addition, phase II/III clinical trials have confirmed that VPA is a safe medicine for the therapy some cancers (43, 44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VPA was used as the total HDACs inhibitor to detect the cardioprotection in the OVE26 type 1 diabetes mice too. Although butyrate was used in the previous studies as total HDAC inhibitor (15), pharmacokinetic studies have confirmed its lower cardiac distribution, compared to VPA (41, 42). In addition, phase II/III clinical trials have confirmed that VPA is a safe medicine for the therapy some cancers (43, 44).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while NaB significantly increases IGF-1 in peripheral tissues in the post stroke animal, there was no elevation of IGF-1 in the brain with this treatment. In a study examining the biodistribution of exogenous fatty acids including n-butyric acid (BA), 4-phenylbutyric acid (PBA) and valproic acid in primates [59], only a very small amount (<0.006%) is taken up by the brain, whereas majority of these fatty acids were taken up by spleen (BA) and liver (PBA). Considering this biodistribution, it is not surprising that NaB was most effective in IGF-1 level in liver, spleen, and serum.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, butyrate has several other pharmacological properties such as anti-infllamatory, antioxidative, immunomodulatory and chemoprotective, which can add further value to subjects with diabetes. However, butyrate has short half-life of 10-15 min due to its rapid uptake and metabolism by normal cells, which dampens its therapeutic utilization [88]. This problem can be overcome with more stable butyrate derivatives like N-(1-carbamoyl-2-phenyl-ethyl) butyramide (FBA or phenylalanine-butyramide), which can provide a consistent effective concentration in systemic circulation [89].…”
Section: Advantages and Limitationsmentioning
confidence: 99%